Pengaruh Kualitas Pelayanan, Harga DAN Store Atmosphere Terhadap Kepuasan Pelanggan Warunk Upnormal Wilayah Jakarta Utara. - Catarina Cori Paramitha; Surya Sumardi (JOURNAL FOR BUSINESS AND ENTREPRENEURSHIP, 2019)
This study aims to determine the effect of service quality, price and store atmosphere on customer satisfaction at Warunk Upnormal North Jakarta. The samples of study are 90 respondent . The sampling method used accidental sampling which sperad off to anyone who met. The research analysis used Structural Equation Modeling (SEM) Analysis and Partial Least Square (PLS) as statistical tools.The data were collected by questionnaire that has been validity and reliability tested. The results of this study revealed that the quality of service has not significant and positive effect on customer satisfaction; price has positive and significant effect on customer satisfaction; store atmosphere has not significant and negative effect on customer satisfaction.Keywords: Quality of Service; Price; Store Atmosphere; Customer satisfaction